WHEN THE DUBBING TURNS THE MALE INTO A FEMALE:: ANTHROPOMORPHY AND GENDER STEREOTYPES FROM THE CARTOON “THE PAW PATROL” - Holzbach, Ariane Diniz; Dornelles, Wagner (Contemporanea, 2022)
This paper seeks to understand the role of anthropomorphism in TV cartoons, considering how it works to uphold gender stereotypes in children’s stories. Instead of neutralizing problematic gender issues, anthropomorphism pedagogically reproduces interpretation models concerning what it means to “be a woman.” To do so, the article discusses the role of anthropomorphism in TV cartoons and then analyzes the construction of characters from PAW Patrol, which, in Brazil, underwent a temporary change of subtitles that changed the genre of two of its six protagonists. It looks into two specific episodes: “Pups Fall Festival” and “Pups Save the Sea Turtles,” which first aired in 2015, but were redubbed due to changes in voice actors. The text also analyzes the comments available on the website Reclame Aqui regarding the season. Technical elements (colors, shape, subtitles), together with the characters’ behavior, express fundamental aspects for understanding current gender roles.